Construction and validity of definitions for outcome indicators of the INICIARE-26 instrument. - Graeff, Murilo dos Santos; Almeida, Miriam de Abreu (Acta Paulista de Enfermagem, 2023)
Objective: To construct and validate with experts the conceptual definitions (CD), operational definitions (OD) and magnitude of the operational definition (MOD) of the 26 outcome indicators of the Nursing Outcomes Classification (NOC), INICIARE-26 instrument components, which measures patients' dependency on nursing care. Methods: A methodological study, in two stages, between January and July 2022. In the first, CD, OD and MOD were developed based on scientific literature. Semantic and conceptual equivalences were observed, in addition to standardization of the indicators' textual formulation. In the second, the Delphi method was used for content validity by eight experts who assessed the relevance of the definitions under the following aspects: "not relevant"; "little relevant"; "quite relevant"; "highly relevant". The Content Validity Index (CVI) was used, with a value greater than 0.78 for agreement analysis. Results: The CD CVI was unanimous for 15 indicators; CD were fully consensual for 17 indicators; MOD was obtained a CVI of 1.00 for 13 indicators. The other items had a CVI of 0.88. The items that did not reach 1.00 of agreement were revised, according to experts' suggestions, with the aim of improving and providing greater clarity for instrument application. Conclusion: The definitions were constructed and, at the time of validity, reached a satisfactory degree of agreement among experts, and some were unanimous.